2019
DOI: 10.1007/s00425-019-03160-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of shade avoidance and shade tolerance in conifers

Abstract: Main conclusion Gymnosperms respond differently to light intensity and R:FR; although some aspects of shade response appear conserved, yet underlying mechanisms seem to be diverse in gymnosperms as compared to angiosperms. Shade avoidance syndrome (SAS) is well-characterized in the shade intolerant model species Arabidopsis thaliana whereas much less is known about shade tolerance response (STR), yet regulation of SAS and STR with reference to conifers remains poorly understood. We conducted a comparative stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 94 publications
9
56
1
Order By: Relevance
“…Norway spruce is a shade tolerant conifer species. It is interesting that in our earlier work we reported that SCRM2, NAC036 and FLZ6 were responsible for the shade tolerant response in Norway spruce (Ranade et al , 2019) and our current finding suggest that missense polymorphisms in these genes show a latitudinal cline in response to shade. DRA2 and PAR2 are the shade responsive genes that were up-regulated under SHADE, in the northern population.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Norway spruce is a shade tolerant conifer species. It is interesting that in our earlier work we reported that SCRM2, NAC036 and FLZ6 were responsible for the shade tolerant response in Norway spruce (Ranade et al , 2019) and our current finding suggest that missense polymorphisms in these genes show a latitudinal cline in response to shade. DRA2 and PAR2 are the shade responsive genes that were up-regulated under SHADE, in the northern population.…”
Section: Discussionsupporting
confidence: 59%
“…Overexpression of NAC036 resulted in a dwarf phenotype in A. thaliana (Kato et al , 2010). This gene was found to be associated with the shade tolerant response in Norway spruce were it was reported to be up-regulated under SHADE conditions (Ranade et al , 2019). In the current work, NAC036 was up-regulated in response to SHADE in the northern trees as compared to the southern ones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of genes related to photosystem I and photosystem II could be affected by various light conditions (Rogowski et al, 2019). Shade avoidance and tolerance responses in plants could be reflected in the alteration of expressed genes, such as those involved in hormone signaling and pigment biosynthesis (Ranade, Delhomme, & García‐Gil, 2019).…”
Section: Introductionmentioning
confidence: 99%